2014
DOI: 10.1371/journal.pone.0098357
|View full text |Cite
|
Sign up to set email alerts
|

Echinococcus P29 Antigen: Molecular Characterization and Implication on Post-Surgery Follow-Up of CE Patients Infected with Different Species of the Echinococcus granulosus Complex

Abstract: The protein P29 is a potential serological marker for post-treatment monitoring of cystic echinococcosis (CE) especially in young patients. We now have demonstrated that P29 is encoded in the Echinococcus genus by a single gene consisting of 7 exons spanning 1.2 kb of DNA. Variability of the p29 gene at inter- and intra-species level was assessed with 50 cDNA and 280 genomic DNA clones isolated from different E. granulosus s.l. isolates (E. granulosus sensu stricto (G1), E. equinus (G4), E. ortleppi (G5), E. c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 52 publications
(68 reference statements)
0
23
0
1
Order By: Relevance
“…Echinococcus granulosus P29 antigen has proved useful for diagnosis and posttreatment monitoring of CE patients (15)(16)(17)29). This study provides evidence that TsMEndoB1 may be applicable for serodiagnosis of NC and other Taeniidae infections, such as CE and AE.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Echinococcus granulosus P29 antigen has proved useful for diagnosis and posttreatment monitoring of CE patients (15)(16)(17)29). This study provides evidence that TsMEndoB1 may be applicable for serodiagnosis of NC and other Taeniidae infections, such as CE and AE.…”
Section: Discussionmentioning
confidence: 79%
“…In the course of our experiments, we cloned and expressed E. granulosus endophilin B1 and observed that the protein exhibited comparable diagnostic sensitivity and specificity, compared with rTsMEndoB1, in diagnosing NC, CE, and AE (data not shown). Several different strains of E. granulosus complex and E. multilocularis that were examined harbored endophilin B1 orthologs that shared 97.9 to 99.6% sequence identity (29). We surmise that these endophilin B1 proteins may also be useful as biomarkers for the detection of specific antibodies in patients with NC, CE, and AE.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Serum samples were examined by ELISA to measure specific IgG and IgG4 antibodies against both the 2B2t and the EgP29 antigens. Serological testing was performed at the Instituto de Recursos Naturales y Agrobiología de Salamanca (IRNASA‐CSIC), Salamanca, Spain.…”
Section: Methodsmentioning
confidence: 99%
“…We tested two recombinant antigens, EgP29 and the novel 2B2t , in a clinically well‐defined patient cohort to address the following question: Does serology reproduce surgical cure as defined by imaging?…”
Section: Introductionmentioning
confidence: 99%